Identification and Screening of Pathogenic Microbes in Oral Smokers - Rizka Efi Mawli; Devi Anggraini Putri; Dwi Aprilia Anggraini; Nadya Dewi Arimbi; Sofiah; Eny Susanti (The Indonesian Institute of Science and Technology Research, 2025)
Smoking has been shown to adversely affect the oral cavity by altering its physiological conditions, thereby promoting the growth of pathogenic microorganisms and increasing the risk of oral diseases. It also reduces salivary pH, rendering it more acidic, and facilitates plaque accumulation. This study aimed to identify the presence of pathogenic microorganisms (Staphylococcus spp., Candida spp., and Entamoeba gingivalis) in the saliva and oral cavity of individuals who smoke. An analytical survey with a cross-sectional design was conducted using 40 samples. Microbial identification was carried out through culture techniques on specific media for bacteria and fungi, while E. gingivalis was detected via direct microscopic observation using safranin staining. 40 samples were analyzed and showed 31 tested positive for at least one of the target microorganisms: Staphylococcus spp., Candida spp., or E. gingivalis, from both saliva and oral swab specimens. Staphylococcus sp. and Candida sp, detected in 13 samples. E. gingivalis was identified in 7 samples. Saliva samples yielded more comprehensive results than oral swabs, suggesting that saliva more accurately reflects the overall microbial condition of the oral cavity.